Lithium-rich manganese positive electrode material as well as surface modification method and application thereof

Through coprecipitation reaction and wet chemical surface modification, the problems of low Coulomb efficiency and cyclic degradation of single crystal lithium-rich manganese-based cathode materials were solved, and higher first Coulomb efficiency and cyclic stability were achieved.

CN119797445AActive Publication Date: 2025-04-11SOUTHWEST PETROLEUM UNIV

Patent Information

Application Number
CN202411940416.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The single crystal lithium-rich manganese-based positive electrode material has low Coulomb efficiency during the initial charging process, and the capacity and voltage continue to degrade during the cycle, mainly due to irreversible oxygen release, TM ion migration and positive electrode-electrolyte interface side reactions.

Method used

Lithium-rich manganese-based precursor was prepared by co-precipitation reaction, and after sintering with the lithium source and molten salt, ammonium dihydrogen phosphate was used as the surface modifier, and the surface was modified by a combination of wet chemistry and heat treatment to form a protective layer to reduce side reactions.

Benefits of technology

The first Coulomb efficiency and cycle stability of lithium-rich manganese cathode material is significantly improved, extending the cycle life of the battery and improving stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797445A_ABST
    Figure CN119797445A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-manganese-rich positive electrode material as well as a surface modification method and application thereof, and belongs to the technical field of preparation of battery positive electrode materials. The preparation method comprises the following specific processes: (1) stirring, dispersing and dissolving nickel salt, cobalt salt and manganese salt, and then adding a precipitator and a complexing agent to prepare a lithium-rich manganese-based precursor; (2) mixing the lithium-rich manganese-based precursor, a lithium source and fused salt, and calcining to obtain a single-crystal lithium-rich manganese-based oxide material; (3) stirring and reacting the single crystal lithium-rich manganese-based oxide material and a surface modifier through a wet chemical method to prepare coated precursor powder; and (4) grinding and calcining the coated precursor powder prepared in the step (3) to prepare the surface-modified lithium-manganese-rich positive electrode material. The preparation method provided by the invention is low in raw material cost, the in-situ surface modification adopts the combination of a wet chemical method and heat treatment, the operation is simple, the production environment requirement is low, the first coulombic efficiency and the cycling stability of the lithium-rich manganese-based positive electrode material are effectively improved, and the preparation method is suitable for large-scale batch production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery positive electrode material preparation, and specifically relates to a lithium-manganese-rich positive electrode material and a surface modification method and application thereof. Background Art

[0002] Lithium-rich manganese-based hierarchical oxide cathode materials have been recognized as one of the most promising cathode materials for the next generation of lithium-ion batteries due to their high specific capacity (over 250 mAh / g) and energy density (over 1000 Wh / kg), as well as environmental friendliness and low cost. Single-crystal lithium-rich manganese cathode materials have micron or submicron-sized particles, each of which consists of only a small number of crystals, rather than many nanocrystals of traditional cathode particles. The single crystal morphology limits surface reactivity and particle cracking, and has greater compaction density and better cycle performance.

[0003] Despite these advantages, single-crystal Li-rich manganese-based cathode materials still have inherent disadvantages, such as low initial Coulombic efficiency and continuous capacity and voltage degradation during cycling. Especially during the initial charging process, Li2MnO3 undergoes irreversible activation reactions, resulting in significant capacity loss. This capacity loss is irreversible and has a great impact on the overall performance of the battery. These weaknesses are mainly due to irreversible oxygen release, TM ion migration, and cathode-electrolyte interface side reactions.

[0004] Doping and surface modification are two effective strategies to solve these problems and improve the performance of single-crystal lithium-rich manganese-based cathode materials. Surface modification technology has significant advantages over other modification methods. It can form a protective layer on the surface of the cathode material, reduce direct contact with the electrolyte, thereby alleviating the generation of side reactions and improving the initial coulombic efficiency. At the same time, it can also effectively enhance the structural stability of the material and prevent it from changing during the charge and discharge process, thereby improving the cycle life and stability of the battery.

[0005] However, most surface-modified materials cannot significantly improve the first coulombic efficiency and cycle life, and have problems such as complicated preparation process, low mechanical strength, and uneven surface coating. In addition, there are few reports on in-situ modification by wet chemical methods. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a lithium-rich manganese positive electrode material and a surface modification method and use thereof, which can effectively improve the first coulombic efficiency and cycle life of the lithium-rich manganese positive electrode material.

[0007] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is: The object of the present invention is to provide a method for surface modification of lithium-rich manganese positive electrode materials, comprising the following steps: (1) stirring and dispersing nickel salt, cobalt salt and manganese salt in water to obtain a mixed metal salt solution, then adding a precipitant and a complexing agent to obtain a lithium-rich manganese-based precursor through a coprecipitation reaction; (2) After mixing the lithium-rich manganese-based precursor, the lithium source and the molten salt, calcining them in an oxygen environment at 500-550°C for 5-8 hours, then heating them to 900-950°C and continuing to calcine for 10-15 hours to obtain a single crystal lithium-rich manganese-based oxide material; (3) stirring the single crystal lithium-rich manganese-based oxide material and the surface modifier by a wet chemical method for 2 to 5 hours, and then heating and stirring until the solvent is completely evaporated to obtain a coating precursor powder; (4) Grinding the coated precursor powder obtained in step (3), calcining at 400-600° C. for 2-6 hours to complete surface modification, and obtaining a surface-modified lithium-rich manganese positive electrode material.

[0008] Furthermore, the mass ratio of manganese element contained in the lithium-rich manganese-based precursor is 50%-60%, the mass ratio of nickel element and cobalt element is 5%-15%, and the particle size is 4-8μm.

[0009] Furthermore, the molar ratio of the nickel salt, the cobalt salt and the manganese salt is 0.1-0.3:0.1-3:0.3-0.8.

[0010] Furthermore, the molar ratio of the nickel salt, the cobalt salt and the manganese salt is 0.25:0.15:0.6.

[0011] Further, the nickel salt is one or more of nickel sulfate, nickel nitrate, nickel acetate and nickel chloride; The cobalt salt is one or more of cobalt sulfate, cobalt nitrate, cobalt acetate and cobalt chloride; The manganese salt is one or more of manganese sulfate, manganese nitrate, manganese acetate and manganese chloride.

[0012] Furthermore, the precipitant is sodium carbonate or sodium bicarbonate; and the complexing agent is ammonia water, ammonium carbonate or ammonium bicarbonate.

[0013] Furthermore, the mass ratio of the lithium-rich manganese-based precursor, the lithium source and the molten salt is 1.5~2:0.5~1:3~4.

[0014] Furthermore, the mass ratio of the lithium-rich manganese-based precursor, the lithium source and the molten salt is 2:0.5:4.

[0015] Further, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium nitride, lithium hydride, lithium oxide, lithium amide, methyl lithium and hexyl lithium; The molten salt is one or more of potassium chloride, sodium chloride, lithium sulfate and lithium chloride.

[0016] Furthermore, in step (2), the calcination is first carried out at a constant temperature of 500° C. for 5 h, and then the temperature is increased to 900° C. and the calcination is continued at a constant temperature for 12 h.

[0017] Furthermore, the mass ratio of the single crystal lithium-rich manganese-based oxide material to the surface modifier is 1:0.01~0.1.

[0018] Furthermore, the surface modifier is ammonium dihydrogen phosphate, and its concentration after dissolution is 0.1~1 mol / L.

[0019] Furthermore, when the wet chemical reaction is carried out in step (3), the rotation speed of the mechanical stirring is 500-800 rpm, and the time of the mechanical stirring is 2-5 hours.

[0020] Furthermore, the temperature of heating and stirring in step (3) is 40°C~80°C, and the speed of mechanical stirring is 700~1000rpm; the temperature of drying after the solvent is completely evaporated is 70°C~80°C.

[0021] Furthermore, in step (3), the coating layer formed by the surface modifier on the surface of the single crystal lithium-rich manganese-based oxide material has a thickness of 5 to 15 nm, and the coating layer after sintering in step (4) has a thickness of 5 to 20 nm.

[0022] Another object of the present invention is to provide a lithium-rich manganese positive electrode material that has been surface-modified, which is prepared using the above-mentioned modification method.

[0023] Another object of the present invention is to provide a use of the above-mentioned lithium-manganese-rich positive electrode material in the preparation of electrode materials or lithium-ion batteries.

[0024] Beneficial effects of the present invention: The present invention provides a surface-modified single-crystal lithium-rich manganese positive electrode material and a preparation method thereof, wherein a nickel source, a cobalt source, and a manganese source are dissolved together in a metal salt solution in deionized water to carry out a coprecipitation reaction to prepare a lithium-rich manganese-based precursor, which is sintered with a lithium source and a molten salt to obtain a single-crystal lithium-rich manganese-based positive electrode material, and a diammonium hydrogen phosphate solution is used as a surface modifier, and the positive electrode material and the surface modifier are reacted by a wet chemical method, and then dried and sintered to perform surface modification, thereby successfully preparing a surface-modified single-crystal lithium-rich manganese positive electrode material, which effectively improves the first coulombic efficiency and cycle stability of the lithium-rich manganese-based positive electrode material.

[0025] The preparation method provided by the present invention has low raw material cost, in-situ surface modification adopts a combination of wet chemical method and heat treatment, is simple to operate, has low requirements on the production environment, effectively improves the first coulombic efficiency and cycle stability of the lithium-rich manganese-based positive electrode material, and is suitable for large-scale batch production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1This is a SEM image of the surface-modified single-crystalline lithium-rich manganese-based oxide material prepared in Example 1; Figure 2 This is a SEM image of the unmodified lithium-rich positive electrode material prepared in Comparative Example 1; Figure 3 It is a comparison diagram of the first charge and discharge curves of Example 1 and Comparative Example 1; Figure 4 The figure is a comparison chart of the cycle performance of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0027] The specific implementation modes of the present invention are described below to facilitate those skilled in the art to understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0028] Example 1 A surface-modified lithium-manganese-rich positive electrode material, the preparation method of which is as follows: (1) A mixed salt solution with a total mass concentration of metal ions of 100 g / L (the molar ratio of Ni ions, Co ions and Mn ions is 0.25:0.15:0.60), a 2 mol / L sodium carbonate solution and a 0.5 mol / L ammonia solution are introduced into the reaction bottom liquid in parallel, and the introduction process is accompanied by stirring. The temperature is controlled at 55° C., the pH is between 7.5 and 8.5, and the stirring speed is 600 rpm to perform a co-precipitation reaction to obtain a precipitate that is a lithium-rich manganese-based precursor material; (2) Weigh 10 g of the above-mentioned lithium-rich manganese-based precursor, 5 g of lithium hydroxide and 20 g of potassium chloride, grind and mix them evenly, keep them at 500° C. for 5 h in an oxygen atmosphere, keep them at 900° C. for 12 h until they are naturally cooled, grind and dry them to obtain a single crystal lithium-rich manganese-based oxide material.

[0029] (3) Dissolve 0.03 g of ammonium dihydrogen phosphate in 30 mL of alcohol and stir for 1 h at a stirring speed of 800 rpm to obtain a surface coating modifier; then add 1 g of the above-mentioned single crystal lithium-rich manganese-based oxide, heat and stir until the solvent is completely evaporated, the heating temperature is 60°C, and the stirring speed is 1000 rpm to obtain a coating precursor.

[0030] (4) The above-mentioned precursor powder is ground and sintered at a temperature of 500°C for 5 hours to finally obtain a surface-modified single-crystalline lithium-rich positive electrode material.

[0031] Example 2 A surface-modified lithium-manganese-rich positive electrode material, the preparation method of which is as follows: (1) A mixed salt solution with a total mass concentration of metal ions of 100 g / L (the molar ratio of Ni ions, Co ions and Mn ions is 0.25:0.25:0.50), a 2 mol / L sodium carbonate solution and a 0.5 mol / L ammonia solution are introduced into the reaction bottom liquid in parallel, and the introduction process is accompanied by stirring. The temperature is controlled at 55° C., the pH is between 7.5 and 8.5, and the stirring speed is 600 rpm to perform a co-precipitation reaction to obtain a precipitate that is a lithium-rich manganese-based precursor material; (2) Weigh 16 g of the above-mentioned lithium-rich manganese-based precursor, 7 g of lithium hydroxide and 35 g of potassium chloride, grind and mix them evenly, keep them at 550° C. for 56 h in an oxygen atmosphere, keep them at 950° C. for 10 h until they are naturally cooled, grind and dry them to obtain a single crystal lithium-rich manganese-based oxide material.

[0032] (3) Dissolve 0.03 g of ammonium dihydrogen phosphate in 30 mL of alcohol and stir for 1 h at a stirring speed of 800 rpm to obtain a surface coating modifier; then add 1 g of the above-mentioned single crystal lithium-rich manganese-based oxide, heat and stir until the solvent is completely evaporated, the heating temperature is 60°C, and the stirring speed is 1000 rpm to obtain a coating precursor.

[0033] (4) The precursor powder is ground and sintered at a temperature of 400°C for 6 hours to obtain a surface-modified single crystal lithium-rich cathode material.

[0034] Example 3 A surface-modified lithium-manganese-rich positive electrode material, the preparation method of which is as follows: (1) A mixed salt solution with a total mass concentration of metal ions of 100 g / L (the molar ratio of Ni ions, Co ions and Mn ions is 0.25:0.15:0.60), a 2 mol / L sodium carbonate solution and a 0.5 mol / L ammonia solution are introduced into the reaction bottom liquid in parallel, and the introduction process is accompanied by stirring. The temperature is controlled at 55° C., the pH is between 7.5 and 8.5, and the stirring speed is 600 rpm to perform a co-precipitation reaction to obtain a precipitate that is a lithium-rich manganese-based precursor material; (2) Weigh 15 g of the above-mentioned lithium-rich manganese-based precursor, 5 g of lithium hydroxide and 30 g of potassium chloride, grind and mix them evenly, keep them at 520° C. for 8 h in an oxygen atmosphere, keep them at 920° C. for 15 h until they are naturally cooled, grind and dry them to obtain a single crystal lithium-rich manganese-based oxide material.

[0035] (3) Dissolve 0.03 g of ammonium dihydrogen phosphate in 30 mL of alcohol and stir for 1 h at a stirring speed of 800 rpm to obtain a surface coating modifier; then add 1 g of the above-mentioned single crystal lithium-rich manganese-based oxide, heat and stir until the solvent is completely evaporated, the heating temperature is 60°C, and the stirring speed is 1000 rpm to obtain a coating precursor.

[0036] (4) The above-mentioned precursor powder is ground and sintered at a temperature of 600°C for 5 hours to finally obtain a surface-modified single-crystalline lithium-rich positive electrode material.

[0037] Comparative Example 1 A lithium-manganese-rich positive electrode material that has not been subjected to surface modification treatment is prepared according to the method of Example 1, except that the surface modification of steps (3) and (4) is not performed, and the other steps are the same as those of Example 1.

[0038] Comparative Example 2 The method of Example 1 is used, except that: in step (3), 10 g of lithium-rich manganese-based precursor, 2.5 g of lithium hydroxide and 20 g of potassium chloride are weighed, ground and mixed evenly, kept at 500° C. for 5 h in an oxygen atmosphere, kept at 900° C. for 12 h, cooled naturally, and ground and dried. The other steps are the same as those of Example 1.

[0039] Comparative Example 3 The method of Example 1 is used, except that: in step (3), 10 g of lithium-rich manganese-based precursor, 7.5 g of lithium hydroxide and 20 g of potassium chloride are weighed, ground and mixed evenly, kept at 500° C. for 5 h in an oxygen atmosphere, kept at 900° C. for 12 h, cooled naturally, and ground and dried. The other steps are the same as those of Example 1.

[0040] Comparative Example 4 The method of Example 1 is used, except that: in step (2), 10 g of the precursor, 5 g of lithium hydroxide and 10 g of potassium chloride are ground and mixed evenly, and then naturally cooled to room temperature after heating and reaction, ground and dried, and collected to obtain a single crystal lithium-rich manganese-based material. The other steps are the same as in Example 1.

[0041] Comparative Example 5 The method of Example 1 is used, except that: in step (2), 10 g of the precursor, 5 g of lithium hydroxide and 30 g of potassium chloride are ground and mixed evenly, and then naturally cooled to room temperature after heating and reaction, ground and dried, and collected to obtain a single crystal lithium-rich manganese-based material. The other steps are the same as in Example 1.

[0042] Comparative Example 6 The method of Example 1 is used, except that: in step (2), the temperature is kept at 500° C. for 5 h, and then kept at 800° C. for 12 h under an oxygen atmosphere, and then naturally cooled, ground and dried to obtain a single crystal lithium-rich manganese-based oxide material. The other steps are the same as those of Example 1.

[0043] Comparative Example 7 The method of Example 1 is used, except that: in step (2), the temperature is kept at 500° C. for 5 h, and then kept at 1000° C. for 12 h under an oxygen atmosphere, and then naturally cooled, ground and dried to obtain a single crystal lithium-rich manganese-based oxide material. The other steps are the same as those of Example 1.

[0044] Comparative Example 8 The method of Example 1 is followed, except that: in step (3), 0.01 g of ammonium dihydrogen phosphate is dissolved in 30 mL of alcohol and mixed and stirred for 1 h at a stirring speed of 800 rpm to obtain a surface coating modifier; the other steps are the same as in Example 1.

[0045] Comparative Example 9 The method of Example 1 is followed, except that in step (4), the sintering temperature is 300° C. and the holding time is 5 h, and finally a surface-modified single crystal lithium-rich positive electrode material is obtained; the other steps are the same as in Example 1.

[0046] Comparative Example 10 The method of Example 1 is followed, except that in step (4), the sintering temperature is 700° C. and the holding time is 5 h, and finally a surface-modified single crystal lithium-rich positive electrode material is obtained; the other steps are the same as in Example 1.

[0047] The surface-modified single-crystalline lithium-rich manganese-based oxide material of Example 1 and the surface-unmodified single-crystalline lithium-rich positive electrode material of Comparative Example 1 were observed using a scanning electron microscope. Figure 1 and Figure 2 shown.

[0048] The positive electrode material prepared in Example 1 was mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 8:1:1, and N-methylpyrrolidone was added as a dispersant to grind into a slurry; then the slurry was evenly coated on one side of the aluminum foil, vacuum dried at 120°C for 10 hours, and the dried electrode was rolled with a roller machine. The aluminum foil was cut with a slicer to form a circular electrode with a diameter of 1.2 cm. The loading amount of the active material was controlled at 5 mg / cm 2 About. A liquid battery was assembled in an argon atmosphere glove box, wherein a lithium sheet with a diameter of 1.6 cm was used as the negative electrode, a 12 μm PP / PE film was used as the separator, and 10 μL of 1 mol / L LiPF6 electrolyte was dripped at the interface between the positive electrode sheet, the lithium negative electrode and the electrolyte, and a CR2032 button cell was assembled in an environment with a water partial pressure of ≤0.1 ppm and an oxygen partial pressure of ≤0.1 ppm. The preparation method of the button cell in Examples 2-3 and Comparative Examples 1-10 is the same as that in Example 1.

[0049] The button cells prepared in Example 1 and Comparative Example 1 were subjected to the first charge and discharge efficiency test, the first discharge capacity test and the cycle performance test respectively. The test conditions were LR 2032. The test results are shown in Figure 3 and Figure 4 , the specific process is as follows: The cycle performance test method is: at 25°C, charge the button battery at 1C and discharge at 1C for 100 cycles with a voltage range of 2.0V-4.8V.

[0050] The first charge and discharge efficiency test and the first discharge capacity test method are as follows: at 25°C, charge the button battery at 0.1C and discharge at 0.1C for 1 week with a voltage range of 2.0V-4.8V.

[0051] like Figure 3 and Figure 4 As shown in the test results, the first discharge, first efficiency and cycle performance of the lithium-rich positive electrode material prepared in Example 1 of the present invention are significantly better than those in Comparative Example 1. Compared with Comparative Example 1, the first coulombic efficiency of Example 1 is increased from 69.5% to 78.7%, the first discharge specific capacity is increased from 251 mAh / g to 263 mAh / g, and the capacity retention rate after 100 cycles of charge and discharge is increased from 85.4% to 94.1%, indicating that surface coating modification has a good effect of improving capacity and inhibiting cycle attenuation.

[0052] The lithium-rich manganese-based positive electrode materials of the above-mentioned Examples 1-3 and Comparative Examples 1-10 were tested at 25° C. The test results are shown in Table 1.

[0053] Table 1 Electrochemical properties of unmodified and modified lithium-rich manganese-based lithium battery cathode materials

[0054] It can be seen from Table 1 that the modification method provided by the present invention effectively improves the first coulombic efficiency and high voltage cycle performance of the lithium battery positive electrode material at room temperature, indicating that the modification method can effectively improve the interface stability of the battery.

[0055] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A surface modification method for a lithium-rich manganese positive electrode material, characterized in that: The following steps are involved: (1) stirring and dispersing nickel salt, cobalt salt and manganese salt in water to obtain a mixed metal salt solution, then adding a precipitant and a complexing agent to obtain a lithium-rich manganese-based precursor through a coprecipitation reaction; (2) After mixing the lithium-rich manganese-based precursor, the lithium source and the molten salt, calcining them in an oxygen environment at 500-550°C for 5-8 hours, then heating them to 900-950°C and continuing to calcine for 10-15 hours to obtain a single crystal lithium-rich manganese-based oxide material; (3) stirring the single crystal lithium-rich manganese-based oxide material and the surface modifier by a wet chemical method for 2 to 5 hours, and then heating and stirring until the solvent is completely evaporated to obtain a coating precursor powder; (4) Grinding the coated precursor powder obtained in step (3), calcining at 400-600° C. for 2-6 hours to complete surface modification, and obtaining a surface-modified lithium-rich manganese positive electrode material.

2. The surface modification method according to claim 1, characterized in that: The molar ratio of the nickel salt, the cobalt salt and the manganese salt is 0.1-0.3:0.1-3:0.3-0.

8.

3. The surface modification method according to claim 1 or 2, characterized in that: The nickel salt is one or more of nickel sulfate, nickel nitrate, nickel acetate and nickel chloride; The cobalt salt is one or more of cobalt sulfate, cobalt nitrate, cobalt acetate and cobalt chloride; The manganese salt is one or more of manganese sulfate, manganese nitrate, manganese acetate and manganese chloride.

4. The surface modification method according to claim 1, characterized in that: The mass ratio of the lithium-rich manganese-based precursor, the lithium source and the molten salt is 1.5~2:0.5~1:3~4.

5. The surface modification method according to claim 4, characterized in that: The lithium source is one or more of lithium carbonate, lithium hydroxide, lithium nitride, lithium hydride, lithium oxide, lithium amide, methyl lithium and hexyl lithium; The molten salt is one or more of potassium chloride, sodium chloride, lithium sulfate and lithium chloride.

6. The surface modification method according to claim 1, characterized in that: The mass ratio of the single crystal lithium-rich manganese-based oxide material to the surface modifier is 1:0.01-0.

1.

7. The surface modification method according to claim 6, characterized in that: The surface modifier is ammonium dihydrogen phosphate, and its concentration after dissolution is 0.1-1 mol / L.

8. The surface modification method according to claim 1, characterized in that: In step (3), the coating layer formed by the surface modifier on the surface of the single crystal lithium-rich manganese-based oxide material has a thickness of 5 to 15 nm, and the coating layer after sintering in step (4) has a thickness of 5 to 20 nm.

9. A surface-modified lithium-manganese-rich positive electrode material, characterized in that: The modified product is prepared by the modification method described in any one of claims 1 to 8.

10. Use of the lithium-manganese-rich positive electrode material according to claim 9 in the preparation of electrode materials or lithium-ion batteries.

Citation Information

Patent Citations

  • Foamed lithium-enriched manganese-based layered oxide and low-temperature fused salt preparation method

    CN106654250A

  • Preparation and application of single crystal-like lithium-rich layered oxide material

    CN109778301A

  • Preparation method and application of lithium phosphate modified high-nickel lithium nickel cobalt manganate positive electrode material

    CN113782715A

  • Monocrystal-like gradient lithium-rich manganese-based layered oxide surface modification method

    CN114639821A

  • Micron-sized monodisperse lithium-rich manganese-based positive electrode material having twin boundary, and preparation therefor

    WO2024244545A1

Cited By

  • Method for preparing single-crystal-state lithium-rich manganese-based positive electrode material by molten salt method, positive electrode material prepared by method, positive electrode and battery

    CN120914242A

  • Monocrystal lithium-rich manganese-based positive electrode material and preparation method thereof

    CN122117879A